3(h+19)-(-9)=12

Simple and best practice solution for 3(h+19)-(-9)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(h+19)-(-9)=12 equation:


Simplifying
3(h + 19) + -1(-9) = 12

Reorder the terms:
3(19 + h) + -1(-9) = 12
(19 * 3 + h * 3) + -1(-9) = 12
(57 + 3h) + -1(-9) = 12

Multiply -1 * -9
57 + 3h + 9 = 12

Reorder the terms:
57 + 9 + 3h = 12

Combine like terms: 57 + 9 = 66
66 + 3h = 12

Solving
66 + 3h = 12

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-66' to each side of the equation.
66 + -66 + 3h = 12 + -66

Combine like terms: 66 + -66 = 0
0 + 3h = 12 + -66
3h = 12 + -66

Combine like terms: 12 + -66 = -54
3h = -54

Divide each side by '3'.
h = -18

Simplifying
h = -18

See similar equations:

| 5y+4-14-4y= | | 4/3pi8^3 | | 12/150=30/x | | 5x-3(x-4)=-2+4x+10 | | (-9x^6)(-5x^2)= | | 31+6n=15n+20 | | -14=-20y-7 | | 2898x-3450=46(63x-75) | | a*4=20 | | z*3+5(z+3)-4(2-2z*2)= | | 4mx/4d^4 | | 6c+-c=20 | | x-3=16-9 | | ln(5-4x)=-3 | | 24-(x-2)=7 | | x+1+x+2+x+7+x+10=360 | | x^2+10x+11=11+x^2+25-25 | | 1/4x-3/2=1/4 | | 2189x^64+50x-12=0 | | x^2+10x+11=11+x^2-25 | | (e^9x+9)-7=0 | | f(x)=-sin | | .06(y-5)+.14y=0.12y-0.6 | | 10-10=-2(8x-4) | | 4a+a*2= | | 2d+8=36 | | 7.8x=x+2.3 | | 2d+8=36-d | | -50+19=180 | | 3(X-3)=36-6X | | X^2+4X+3X=0 | | 3x+1+2x-3+x+7=180 |

Equations solver categories